Kematangan Emosi Remaja Pelaku Bullying - Maryam, Siti; Fatmawati, Fatmawati (Jurnal Kajian Bimbingan dan Konseling, 2018)
In recent year, there is a number of news in the mass media on violence in the school, including bullying. The high number of juvenile delinquency is the result of a lack of ability to control emotions in an acceptable way, causing the individual to easily engage the group's influence to perform negative behavior, including bullying behavior. From the above explanation, we interested to examine more deeply how the emotional maturity in adolescents bully in Junior High School 9 Banda Aceh. This study was done through quantitave method by using using the Emotional Maturity scale developed by Katkovsky and Gorlow. The results showed that most of the students had emotional maturity belonging to the low category with the percentage of 80.65%. To that end, parents and teachers have a very important role, in which they must be consistent in educating, being open and dialogical, not authoritarian, or imposing a will to the adolescents.